2019
DOI: 10.1097/txd.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Contemporary Graft Survival for Adult Liver Retransplantation: An Australian and New Zealand Registry Analysis From 1986 to 2017

Abstract: Background. Liver retransplantation is technically challenging, and historical outcomes are significantly worse than for first transplantations. This study aimed to assess graft and patient survival in all Australian and New Zealand liver transplantation units. Methods. A retrospective cohort analysis was performed using data from the Australia and New Zealand Liver Transplant Registry. Graft and patient survival were analyzed according to era. Cox regression was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
5
14
0
Order By: Relevance
“…Temporally, we noted that the frequency of retransplantation has steadily increased in Canada from 9 cases in 2000 to 31 cases in 2018, with approximately 0.2% yearly increase in retransplantation rates. Similarly, Australia and New Zealand have also noticed an increase in retransplantation since 2001 [ 13 ]. Conversely, this has not been the case in Europe, where an analysis of the European Liver Transplant Registry (ELTR) from 2000–2009 revealed a 5% decrease in the utilization of retransplantation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Temporally, we noted that the frequency of retransplantation has steadily increased in Canada from 9 cases in 2000 to 31 cases in 2018, with approximately 0.2% yearly increase in retransplantation rates. Similarly, Australia and New Zealand have also noticed an increase in retransplantation since 2001 [ 13 ]. Conversely, this has not been the case in Europe, where an analysis of the European Liver Transplant Registry (ELTR) from 2000–2009 revealed a 5% decrease in the utilization of retransplantation [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…5 Decompensated cirrhosis (DC) patients often require nutritional support but optimal timing of intervention and outcomes are unclear. 6 1). Prevalence of malnutrition was 76.6% (CI 62-87.6%) which was independent of age or aetiology of liver disease but was associated with disease severity.…”
mentioning
confidence: 99%
“…Graft failure occurs in 5-22% of all liver transplant recipients. [1][2][3][4][5][6] Liver re-transplantation has been considered controversial, with clinical, economic, and ethical considerations. A study from Birmingham in 2009, reported no survival benefit following second and third re-transplantation.…”
mentioning
confidence: 99%
“…Notably, patients with POPH had significantly lower MELD scores at the time of LT, were more likely to be female, had higher pretransplant serum albumin and sodium, and had a higher functional capacity at the time of LT, all of which would be expected to protect against graft failure, and therefore the increased risk of graft failure in patients with POPH is even more striking. (29)(30)(31)(32)(33)(34) Among patients with POPH undergoing LT, we observed a significant association with adverse post-LT outcomes and pre-LT hemodynamics, identifying a pre-LT PVR >1.6 as significantly increasing the risk of post-LT adverse outcomes (death or retransplantation) in patients with POPH. This threshold is lower than expected from similar work recently published by DuBrock et al (20) and Cartin-Ceba et al, (21) who identified a PVR ≥3 WU as predictive for post-LT mortality in patients with POPH and is also lower than the diagnostic criteria currently used to define POPH (MPAP ≥25 mm Hg, PVR ≥3 WU).…”
Section: Discussionmentioning
confidence: 72%